La judicialización de la política en el Perú: Una observación del Tribunal Constitucional y sus decisiones frente a la píldora del día siguiente (2001-2010) - Loaiza, Pamela (2013)
This article analyzes the judicial behavior and the importance of judges in policy making in Peru regarding the case of the magistrates of the Constitutional Tribunal and its decisions regarding the morning after pill. We will focus our research on the shift in orientation of two veredicts issued by this judicial institution; one in favor of its state sponsored distribution (2006) and one against it (2009). In order to analyze the circumstances that led to this two different outcomes, we state that the morning after pill, a case of consciousness, made the judges decide based on their strategic alliances inside the tribunal or their own personal trajectories. In order to solve these dilemmas, the analysis of the kind of judges in the tribunal was crucial to understand the relationship between the elected judges and the interests of political parties in parliament. We believe that the shift in orientation of the veredicts lies in the fact that, for cases of consciousness, the Tribunal uses its sitting judges.